PENGARUH PENDEKATAN HIGH ORDER THINKING SKILL (HOTS) TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI - Siti Rukmini; Rochmat Tri Sudrajat; Latifah Latifah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
Writing is a language skill in expressing main ideas or ideas in writing. Writing skills are not easy to do in learning, this is related to the level of writing at the highest level position. Learning must be done by choosing an approach that can promote students' critical thinking skills. The explanatory text is a text that can express students' ideas in writing about phenomena. Therefore, this study was conducted on the background of how the learning process of writing explanatory text with an approach that can provide a stimulus for critical thinking. The purpose of this study was to determine the explanatory text writing skills influenced by the HOTS approach. The research method used in this study was descriptive qualitative. The subjects of this study were 26 students of class VIII-B of SMPN 2 Margaasih. The results showed that 16 students got high scores, 7 students got adequate scores and 3 students got low scores. The results of the study concluded that the use of HOTS-based approaches in class VIII-B students could improve their explanatory text writing skills.